The Layman's Progress: Religious and Political Experience in Colonial Pennsylvania, 1740-1770 - Rothermund, Dietmar (University of Pennsylvania Press, 2016)
Frontmatter -- Contents -- Preface -- Introduction -- I. Philadelphia and the World -- II. The Implications of the Great Awakening -- III. The New Denominational Consciousness -- IV. The Process of Secularization -- V. Pennsylvania's Political Problems -- VI. Patterns of Leadership -- VII. The Interaction of Groups -- VIII. The Eve of the Revolution -- Conclusions -- Appendix -- Bibliography -- Index